Sensibilidade e especificidade do teste rápido na urina (POC-CCA) e avaliação da morbidade da esquistossomose mansônica em região de baixa prevalência - Fernanda Tavares Ferreira (2016)
Kato-Katz is the most common used diagnostic method for Schistosoma mansoni infection. Day-to-day variability in host egg excretion in the stools and its low detection sensitivity are major limits for its use. In high transmission areas, the urine point-of-care circulating cathodic antigen assay (POC-CCA) has proved to be a reliable test. However, investigations in low transmission regions are lacking. In the present study, we evaluated the sensitivity and specificity of the CCA test in a low endemic area of Brazil. In addition, morbidity of the disease was also analyzed. Pains, a city comprising 8,329 inhabitants is a low transmission zone for schistosomiasis. All people living in 4 districts with 1,637 subjects were enrolled in the study and 300, in the age range of 7 to 76 years (mean = 43.9 years), were randomly selected to test the POC-CCA cassete. For Schistosoma mansoni diagnosis, 3 stool samples with 6 slides for each person were compared with one urine sample. Sensitivity and specificity, in the absence of a gold standard was calculated using the latent class analysis (LCA). Clinical examination and abdominal ultrasound were used to evaluate schistosomal morbidity. The sensitivity and specificity of Kato-Katz technique was 25.6% and 94.6%, respectively. For the sensitivity and specificity using CCA assay, the values were 68.1% and 72.8%, respectively. Hepatosplenic schistosomiasis was diagnosed in 2 patients (1.2%). Overall, CCA urine assay proved to be a useful test for schistosomiasis mansoni diagnosis in a low endemic area of Brazil. Severe hepatosplenic schistosomiasis was uncommon.